Pengaruh Model Pembelajaran Generatif Dengan Teknik Guided Teaching Terhadap Keterampilan Proses Sains - Rasydah Nur Tuada; Gunawan Gunawan; Susilawati Susilawati (Department of Physics Education, Universitas Mataram, 2017)
The purpose of this research is to know the effect of generative learning with guided teaching technique towards science process skills of students high school 7 Mataram. This research is a quasi-experimental with non-equivalent control group design. Population in research is all students class X of high school 7 Mataram. Sampling method is cluster random sampling, with students sample of X-E class (class experiment) and X-C class (class control). Instruments used to measure of the science process skill is a multiple-choice grounded test. The initial ability of the experimental and control classes is homogeneous, so the effect of treatment is the result of the final test. Test the hypothesis using the t-test polled variants. Improved science process skills are determined based on the N-gain test. Interesting findings from the study indicate an increase in the science process skills in both classes. This show the generative learning with guided teaching techniques were applied successfully improve science process skills.